Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Sure, let's break down the process of graphing the system of equations and finding the solution step by step.
We are given the system of equations:
[tex]\[ \begin{array}{l} y = 3x + 9 \\ 6x + 2y = 6 \end{array} \][/tex]
### Step 1: Graph the First Equation
The first equation is:
[tex]\[ y = 3x + 9 \][/tex]
This is a linear equation in slope-intercept form, [tex]\(y = mx + b\)[/tex], where [tex]\(m\)[/tex] is the slope and [tex]\(b\)[/tex] is the y-intercept.
For [tex]\(y = 3x + 9\)[/tex]:
- The slope [tex]\(m = 3\)[/tex]
- The y-intercept [tex]\(b = 9\)[/tex]
To graph this equation, start at the point (0, 9) on the y-axis and use the slope to find another point. The slope of 3 means you rise 3 units for every 1 unit you run to the right. So, starting at (0, 9):
- When [tex]\(x = 1\)[/tex], [tex]\(y = 3(1) + 9 = 12\)[/tex]. (Point is (1, 12))
- When [tex]\(x = -1\)[/tex], [tex]\(y = 3(-1) + 9 = 6\)[/tex]. (Point is (-1, 6))
Draw a line through these points.
### Step 2: Graph the Second Equation
The second equation is:
[tex]\[ 6x + 2y = 6 \][/tex]
First, we convert it to slope-intercept form [tex]\(y = mx + b\)[/tex]:
- Divide the entire equation by 2 to simplify it:
[tex]\[ 3x + y = 3 \][/tex]
- Solve for [tex]\(y\)[/tex]:
[tex]\[ y = -3x + 3 \][/tex]
Now, this is also a linear equation in slope-intercept form with:
- The slope [tex]\(m = -3\)[/tex]
- The y-intercept [tex]\(b = 3\)[/tex]
To graph this equation, start at the point (0, 3) on the y-axis and use the slope to find another point. The slope of -3 means you drop 3 units for every 1 unit you run to the right. So, starting at (0, 3):
- When [tex]\(x = 1\)[/tex], [tex]\(y = -3(1) + 3 = 0\)[/tex]. (Point is (1, 0))
- When [tex]\(x = -1\)[/tex], [tex]\(y = -3(-1) + 3 = 6\)[/tex]. (Point is (-1, 6))
Draw a line through these points.
### Step 3: Determine the Intersection
By graphing both lines, we see where they intersect.
The lines intersect at the point [tex]\((-1, 6)\)[/tex].
Therefore, the solution to the system of equations is:
[tex]\[ (-1, 6) \][/tex]
So, the correct answer is:
- There is one unique solution [tex]\( (-1, 6) \)[/tex].
We are given the system of equations:
[tex]\[ \begin{array}{l} y = 3x + 9 \\ 6x + 2y = 6 \end{array} \][/tex]
### Step 1: Graph the First Equation
The first equation is:
[tex]\[ y = 3x + 9 \][/tex]
This is a linear equation in slope-intercept form, [tex]\(y = mx + b\)[/tex], where [tex]\(m\)[/tex] is the slope and [tex]\(b\)[/tex] is the y-intercept.
For [tex]\(y = 3x + 9\)[/tex]:
- The slope [tex]\(m = 3\)[/tex]
- The y-intercept [tex]\(b = 9\)[/tex]
To graph this equation, start at the point (0, 9) on the y-axis and use the slope to find another point. The slope of 3 means you rise 3 units for every 1 unit you run to the right. So, starting at (0, 9):
- When [tex]\(x = 1\)[/tex], [tex]\(y = 3(1) + 9 = 12\)[/tex]. (Point is (1, 12))
- When [tex]\(x = -1\)[/tex], [tex]\(y = 3(-1) + 9 = 6\)[/tex]. (Point is (-1, 6))
Draw a line through these points.
### Step 2: Graph the Second Equation
The second equation is:
[tex]\[ 6x + 2y = 6 \][/tex]
First, we convert it to slope-intercept form [tex]\(y = mx + b\)[/tex]:
- Divide the entire equation by 2 to simplify it:
[tex]\[ 3x + y = 3 \][/tex]
- Solve for [tex]\(y\)[/tex]:
[tex]\[ y = -3x + 3 \][/tex]
Now, this is also a linear equation in slope-intercept form with:
- The slope [tex]\(m = -3\)[/tex]
- The y-intercept [tex]\(b = 3\)[/tex]
To graph this equation, start at the point (0, 3) on the y-axis and use the slope to find another point. The slope of -3 means you drop 3 units for every 1 unit you run to the right. So, starting at (0, 3):
- When [tex]\(x = 1\)[/tex], [tex]\(y = -3(1) + 3 = 0\)[/tex]. (Point is (1, 0))
- When [tex]\(x = -1\)[/tex], [tex]\(y = -3(-1) + 3 = 6\)[/tex]. (Point is (-1, 6))
Draw a line through these points.
### Step 3: Determine the Intersection
By graphing both lines, we see where they intersect.
The lines intersect at the point [tex]\((-1, 6)\)[/tex].
Therefore, the solution to the system of equations is:
[tex]\[ (-1, 6) \][/tex]
So, the correct answer is:
- There is one unique solution [tex]\( (-1, 6) \)[/tex].
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.